Public Key Encryption with Ranked Multi-keyword Search - Chengyu Hu; Pengtao Liu (2013 5th International Conference on Intelligent Networking and Collaborative Systems, 2013)
It is necessary for the cloud server to allow multi-keyword query and provide result ranking to effectively retrieve data from the large number of encrypted data stored in the cloud storage. A related work that support privacy preserving ranked multi-keyword search over encrypted cloud data (MRSE) is not in public-key model. In this paper, the definition of an extension of PEKS called Public-Key Encryption with Ranked Multi-Keyword Search(PERMKS) is proposed, which means that the receiver could query any subset of keywords and the number of queried keywords appearing in the data can be provided which evaluate the similarity ranking of the data to the search query. Then, a construction of public-key encryption with ranked multikeyword search scheme with sub-linear cipher texts based on anonymous hierarchical identity-based encryption (AHIBE) is put forward and its security is analyzed.